Prescription auditing and observational study in a tertiary care hospital - Gari, Manju; Varshney, Manisha; Lal, Shreya (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Prescription is an important document written by a doctor which if not written properly can lead to various problems such as adverse drug reactions in patients, incompatibility to follow the instructions to take timely medications and sometimes over dosage due to improper prescription can even lead to death of the patient. Methods: This prospective observational cross-sectional study was conducted over a period of 6 months. The study was conducted in Rajendra Institute of Medical Sciences, Ranchi. Various prescriptions were collected from outpatient care facilities of a tertiary care hospital. Results were analyzed and assessed on 150 prescriptions collected. Results: Total 150 prescriptions were evaluated out of which 49.3% were males and 50.7% were females. Various parameters were assessed during the study which showed that there is still a scope of improvement in prescribing patterns in areas of writing complete prescriptions, prescribing generic medications and mentioning drug dosage forms as well as time of administration in each prescription. Conclusions: The results showed there is still a scope of improvement in writing practices of prescription. The doctor should incur the habit of writing generic names of drug in every prescription. They should adopt proper handwriting skills and no mistakes should be done in a prescription. A good prescription written by a doctor will help in legible practice and will also be very helpful in patient’s care.